(untitled) (Scientific journal of the Fergana State University, 2026)
Corruption poses a serious obstacle to the development of modern society and the state, leading to negative consequences in both social and economic spheres. This article is dedicated to analyzing the socio-economic impact of corruption in Uzbekistan and in the global context. The study examines scientific sources, international reports (Transparency International, World Bank), Uzbekistan’s local statistics, and public opinion from various platforms. The findings show that corruption exacerbates social inequality, decreases public trust, reduces investment, and harms the state budget. Although recent reforms in Uzbekistan—particularly initiatives around digitalization and transparency—have produced positive results, the issue remains pressing. On a global scale, Denmark (low corruption) and Nigeria (high corruption) are compared, and digitalization, legal education, and international cooperation are proposed as effective measures. The article emphasizes the importance of strategic approaches in the fight against corruption for Uzbekistan and other developing countries.